Fine Structures of Radio Bursts from Flare Star AD Leo with FAST Observations - Jiale Zhang; Hui Tian; Philippe Zarka; Corentin K. Louis; Hongpeng Lu; Dongyang Gao; Xiaohui Sun; Sijie Yu; Bin Chen; Xin Cheng; Ke Wang (The Astrophysical Journal)
Radio bursts from nearby active M-dwarfs have been frequently reported and extensively studied in solar or planetary paradigms. Whereas, their substructures or fine structures remain rarely explored despite their potential significance in diagnosing the plasma and magnetic field properties of the star. Such studies in the past have been limited by the sensitivity of radio telescopes. Here we report the inspiring results from the high time-resolution observations of a known flare star AD Leo with the Five-hundred-meter Aperture Spherical radio Telescope. We detected many radio bursts in the 2 days of observations with fine structures in the form of numerous millisecond-scale sub-bursts. Sub-bursts on the first day display stripe-like shapes with nearly uniform frequency drift rates, which are possibly stellar analogs to Jovian S-bursts. Sub-bursts on the second day, however, reveal a different blob-like shape with random occurrence patterns and are akin to solar radio spikes. The new observational results suggest that the intense emission from AD Leo is driven by electron cyclotron maser instability, which may be related to stellar flares or interactions with a planetary companion.